Ag2CO3 containing magnetic nanocomposite as a powerful and recoverable catalyst for Knoevenagel condensation - Fatemeh Karimkhah (Nature Portfolio, 2021)
Abstract In this paper, the synthesis, characterization and catalytic application of a novel magnetic silica-supported Ag2CO3 (MS/Ag2CO3) with core–shell structure are developed. The MS/Ag2CO3 nanocomposite was prepared through chemical modification of magnetic MS nanoparticles with AgNO3 under alkaline conditions. The structure, chemical composition and magnetic properties of MS/Ag2CO3 were investigated by using VSM, PXRD, FT-IR, EDX and SEM techniques. The MS/Ag2CO3 nanocomposite was used as an effective catalyst for the Knoevenagel condensation under solvent-free conditions at 60 °C in an ultrasonic bath. The recovery and leaching tests were performed to study the nature of the MS/Ag2CO3 catalyst under applied conditions.